What has religion got to do with it? ethics and attitudes towards corruption in Nigeria (2010)
Based on the salience of religion in public life in Nigeria, alongside the pervasiveness of corruption in the country, it has become imperative to research into the relationship, if any, between religion and corruption and determine if the former has or can have any impact on stemming the later. This is based on a widely held assumption that religion is often positive. In looking at the influence of religion on attitudes to corruption in Nigeria and based on the contents of the research instrument employed for this study, the paper presents findings from the study according to analytical categories. Thus, it discusses respondents' perception of religion and morality (ethics); as well as examines the divide, if at all, between public and private morality; the definitions/explanations of corruption in the religions; religious beliefs and personal attitudes to corruption; the influence that tradition and modernity mayor may not have on corruption; corruption, gender and youth and the role of FBOs and anti-corruption agencies in corruption abatement or promotion. It concludes that while the three main religions under study in Nigeria explicitly condemn corruption, they do not seem to impact or influence attitudes to corruption in any major way. Furthermore, the fact that religious people and religious houses often roundly denounce corruption has not brought about any moderation or diminution of corrupt tendencies in the public space. The paper then pulls together some suggestions for ways to use religion to mitigate the scourge of corruption.